2016
DOI: 10.1007/s00294-016-0566-6
|View full text |Cite
|
Sign up to set email alerts
|

Partial suppression of the respiratory defect of qrs1/her2 glutamyl-tRNA amidotransferase mutants by overexpression of the mitochondrial pentatricopeptide Msc6p

Abstract: Recently, a large body of evidences indicates the existence in the mitochondrial matrix of foci that contain different proteins involved in mitochondrial RNA metabolism. Some of these proteins have a pentatricopeptide repeat motif that constitutes their RNA-binding structures. Here we report that MSC6, a mitochondrial pentatricopeptide protein of unknown function, is a multi copy suppressor of mutations in QRS1/HER2 a component of the trimeric complex that catalyzes the transamidation of glutamyl-tRNAQ to glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Msc6p belongs to the large pentatricopeptide protein family whose members have been shown to interact with and stabilize RNA . Previous studies indicated that ,mutations in MSC6 did not affect transcription, processing or stability of mitochondrial RNAs but did marginally reduce mitochondrial translation . These observations together with the respiratory‐deficient phenotype of the fmt1 msc6 double mutant, suggested a role of Msc6p in mitochondrial protein synthesis.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Msc6p belongs to the large pentatricopeptide protein family whose members have been shown to interact with and stabilize RNA . Previous studies indicated that ,mutations in MSC6 did not affect transcription, processing or stability of mitochondrial RNAs but did marginally reduce mitochondrial translation . These observations together with the respiratory‐deficient phenotype of the fmt1 msc6 double mutant, suggested a role of Msc6p in mitochondrial protein synthesis.…”
Section: Resultsmentioning
confidence: 96%
“…The suppressor properties of MSC6 overexpression over mitochondrial translation defective mutants lead us to investigate putative interactions of MSC6 with other mitochondrial translation mutants, such as fmt1 , msi1 , trm1 , pus5 , oms1 , etc. that were already described in a high throughput study .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PPR proteins have been described in chloroplasts and in plant, human, and fungal mitochondria (Shikanai, 2006; Lipinski et al , 2011; Solotoff et al , 2015). Pet309p, Atp22p, and Msc6p are examples of yeast mitochondrial PPR proteins involved in the stability and/or translation of mitochondrially encoded RNAs (Krause et al , 2004; Zeng et al , 2007; Moda et al , 2016). Like other PPR proteins, Aep3p was recently shown to cosediment with mitochondrial ribosomes in a large complex termed Miorex (Kehrein et al , 2015).…”
Section: Discussionmentioning
confidence: 99%